Analisis Sektor Unggulan Dan Infrastruktur Dalam Peningkatan Pembangunan Ekonomi Kota Jakarta Selatan - Fifi Yulianti; Jihana Tasya Selawijaya; Yulia Putriyani (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to analyze the leading sectors and infrastructure in South Jakarta City in increasing economic development. This study uses secondary data available on the websites of BPS DKI Jakarta and BPS Jakarta Selatan for the period 2017-2021. Analytical tools of this study are Location Quotient (LQ), Shift-Share (SS), Klassen Typology, and Scalogram. So that from the results of this study, it will be concluded which sectors are included in the leading sectors in the city of South Jakarta, and can also find out how the condition of the existing infrastructure in the city of South Jakarta is whether the Neighborhoods have been able to feel the benefits of the existing infrastructure. And this research aims to see whether economic development in South Jakarta City is evenly distributed among the Neighborhoods.